(untitled) (Universal International Scientific Journal, 2026)
The manifestation of bullying among schoolchildren is one of the important problems of the modern education system. Bullying is a continuous or systematic physical, verbal, social and psychological pressure, humiliation, harm to an opponent, violence, exclusion from the group, ostracism or threats. This process is not always consciously perceived by schoolchildren, but the negative consequences of bullying leave a deep imprint on their social and mental life. Such situations directly affect the school environment, students’ daily life and participation in the educational process. The presence of bullying in adolescents and children of primary school age causes psychological crises, low self-esteem, insecurity, depression and behavioral disorders.